2022
DOI: 10.1021/acs.jafc.2c03244
|View full text |Cite
|
Sign up to set email alerts
|

Plant Volatiles Mediate Host Selection of Sitodiplosis mosellana (Diptera: Cecidomyiidae) among Wheat Varieties

Abstract: Sitodiplosis mosellana is a major wheat pest that oviposits on spikes, and resistant wheat varieties have been released. However, wheat spike volatiles mediating S. mosellana host selection or resistance are largely unknown. In this study, we found that the highly susceptible wheat varieties Xinong 822, Xinong 88, and Xiaoyan 22 were preferred for S. mosellana oviposition, and their spike volatiles were more attractive to females compared to the resistant varieties Kenong 1006, Shanmai 139, and Jinmai 47. Impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Among the 102 plant VOCs, α -farnesene was detected in the healthy resistant line only ( Table S10 ). α -farnesene functions to defend plants from insects (Huang et al, 2022). Therefore, we speculated that it also has a repellent effect on S. frugiperda .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 102 plant VOCs, α -farnesene was detected in the healthy resistant line only ( Table S10 ). α -farnesene functions to defend plants from insects (Huang et al, 2022). Therefore, we speculated that it also has a repellent effect on S. frugiperda .…”
Section: Resultsmentioning
confidence: 99%
“…This study investigated the effects of different plant VOCs on the preferences of S. frugiperda . Previous studies have shown that terpenoids are important HIPVs in direct or indirect plant defense, as they not only repel herbivorous insects and also attract predators or parasites of herbivorous insects (Heil, 2008; War et al, 2011; Sharma et al, 2017; Huang et al, 2022). Furthermore, heterocyclic compounds have been reported to be toxic to the larvae of S. frugiperda (Huang et al, 2019; Kim et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Host plant location and selection is a crucial task for herbivorous insects in their search for resources, mates, and oviposition sites; and olfaction typically plays an important role in this process (Song et al 2022). Adults detect volatile organic compounds (VOCs) emitted by plants in a speci c way, discriminating between different resistant plants or cultivars based on the types and proportions of volatile compounds (Ranger et al 2005;Huang et al 2022). Volatiles from non-host plants or resistant cultivars contain repellent components to prevent herbivorous insect infestation (Yuan et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Volatiles from non-host plants or resistant cultivars contain repellent components to prevent herbivorous insect infestation (Yuan et al 2022). For example, Rosmarinus o cinalis, a non-host plant with speci cally bioactive compounds in its volatiles that repelling Ectropis obliqua adults (Zhang et al 2015); ocimene, a dominant component of resistant wheat varieties repelled Sitodiplosis mosellana females (Huang et al 2022). Similarly, attractive components in host volatile blends are the crucial reason why host plants or susceptible cultivars are more susceptible to pest infestation (Birkett et al 2004;Yang et al 2016;Xiu et al 2019).…”
Section: Introductionmentioning
confidence: 99%